2013
DOI: 10.1063/1.4813254
|View full text |Cite
|
Sign up to set email alerts
|

Resonant absorption and not-so-resonant absorption in short, intense laser irradiated plasma

Abstract: An analytical model for laser-plasma interaction during the oblique incidence by an ultrashort ultraintense p-polarized laser on a solid-density plasma is proposed. Both the resonant absorption and not-so-resonant absorption are self-consistently included. Different from the previous theoretical works, the physics of resonant absorption is found to be valid in more general conditions as the steepening of the electron density profile is considered. Even for a relativistic intensity laser, resonant absorption ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…[13][14][15][16][17] In the previous researches, Naumova et al 18 investigated how a p-polarized ultra-intense laser pulse interacting with sharp boundaries of an overdense plasma channel produced electron bunches of attosecond duration. It is shown that, an ultrarelativistic laser pulse focused on the entrance of the channel propagates through the channel and generates attosecond electron beams with an energy of 20-30 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] In the previous researches, Naumova et al 18 investigated how a p-polarized ultra-intense laser pulse interacting with sharp boundaries of an overdense plasma channel produced electron bunches of attosecond duration. It is shown that, an ultrarelativistic laser pulse focused on the entrance of the channel propagates through the channel and generates attosecond electron beams with an energy of 20-30 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (PIC) simulations predict the applications of a fast ignitor mechanism and radiotherapy via ultra-intense laser interaction with an overdense plasma [27]. The physics of resonant absorption of a p-polarized intense laser beam is theoretically presented by Ge et al [28] in solid target plasma. The absorption is very sensitive to the laser intensity and plasma density scale length and is resonant for an incident angle nearly of about 45 • .…”
Section: Introductionmentioning
confidence: 99%
“…In the laser fusion plasma, the absorption is achieved by several mechanisms including inverse bremsstrahlung absorption (IBA) [13][14][15][16], resonance absorption [17,18] and anomalous absorption [19].…”
mentioning
confidence: 99%